Lightning as a space‐weather hazard: UK thunderstorm activity modulated by the passage of the heliospheric current sheet. Issue 22 (19th November 2015) - Owens, M. J.; Scott, C. J.; Bennett, A. J.; Thomas, S. R.; Lockwood, M.; Harrison, R. G.; Lam, M. M.
Abstract: Lightning flash rates, RL, are modulated by corotating interaction regions (CIRs) and the polarity of the heliospheric magnetic field (HMF) in near‐Earth space. As the HMF polarity reverses at the heliospheric current sheet (HCS), typically within a CIR, these phenomena are likely related. In this study, RL is found to be significantly enhanced at the HCS and at 27 days prior/after. The strength of the enhancement depends on the polarity of the HMF reversal at the HCS. Near‐Earth solar and galactic energetic particle fluxes are also ordered by HMF polarity, though the variations qualitatively differ from RL, with the main increase occurring prior to the HCS crossing. Thus, the CIR effect on lightning is either the result of compression/amplification of the HMF (and its subsequent interaction with the terrestrial system) or that energetic particle preconditioning of the Earth system prior to the HMF polarity change is central to solar wind lightning coupling mechanism. Key Points: UK lightning is enhanced when the Earth intersects the heliospheric current sheet Lightning rates depend on the polarity of the heliospheric magnetic field Associated changes in the energetic particle populations are complex